2018
DOI: 10.1016/j.amjsurg.2017.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Does a balanced transfusion ratio of plasma to packed red blood cells improve outcomes in both trauma and surgical patients? A meta-analysis of randomized controlled trials and observational studies

Abstract: High FFP:RBC ratio confers survival benefits in trauma and non-trauma settings, with the highest survival benefit at 1:1.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
3
26
0
2
Order By: Relevance
“…This is the first meta‐analyses to report exposure to allogeneic blood products in resuscitation using fixed component transfusion ratios. This review also updates the evidence previously published in other systematic reviews . In addition, this is the first review assessing transfusion ratios of FFP and PLT in trauma patients exclusively and to use the GRADE profile to assess the evidence in trauma patients.…”
Section: Discussionsupporting
confidence: 52%
“…This is the first meta‐analyses to report exposure to allogeneic blood products in resuscitation using fixed component transfusion ratios. This review also updates the evidence previously published in other systematic reviews . In addition, this is the first review assessing transfusion ratios of FFP and PLT in trauma patients exclusively and to use the GRADE profile to assess the evidence in trauma patients.…”
Section: Discussionsupporting
confidence: 52%
“…The goal of the present study was to use a large French multicenter prospective trauma registry to evaluate the association of an early (ie, first 6 hours), high FFP-to-PRBC transfusion ratio (ie, a mean of >2 FFP to 3 PRBC 33 ) with 30-day survival in patients with severe bleeding after trauma while accounting for confounders.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits associated with this approach have been evaluated in different clinical settings, including adult trauma patients, adult cardiac surgery patients, patients undergoing nontrauma massive transfusion and patients with ruptured abdominal aortic aneurysms . Furthermore, a recent meta‐analysis evaluating the benefits of a balanced transfusion ratio in trauma and surgical patients concluded that high plasma to red blood cell transfusion ratio was associated with improved survival at 24 h and 30 days mortality . However, this approach cannot be generalized to all bleeding patients needing transfusion.…”
Section: Introductionmentioning
confidence: 99%